(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper focuses on the optimization of drilling process parameters using the Fuzzy-Taguchi technique to obtain minimum surface roughness (Ra) and maximum Material Removal Rate (MRR). A number of drilling experiments were conducted using the L9 Orthogonal Array on a conventional machining center. The experiments were conducted on Aluminium Alloy 7075 material blocks using three types of drill bits under wet cutting conditions. A Design of Experiment was employed to determine the most significant control the factors affecting the Surface Roughness and Material Removal Rate. The Cutting Tool, Cutting Speed and Coolant were selected as the control factors. After the nine experimental trails, the most significant factor on the surface roughness and the material removal rate was found